Research of influence of natural and climatic conditions, social and economical activities on the functioning of the territories - Хапов, Денис Викторович (Technology audit and production reserves, 2015)
The fact, that natural and climatic factors (NCF) play significant role in the life of a society and a State, they are one of the most important environmental factors, ignoring that can be especially dangerous for village, water, recreational economy, transport and energetic systems, construction, communal economy and industry is realizing at the heart of the article. Actuality of these researches lies in the fact the stable development and effective functioning of economy dictates necessity of calculation of NCF and dynamics of their influence, as well as for the tasks of national and regional scale. It is advisable to apply this information also in the process of development, planning, projecting, operations of agricultural, industrial, transport, construction organizations and enterprises for working out of adaptation as well as on the country and regional levels. The analysis of different rating assessments was worked out minimum necessary set of criteria-indices of system of assessment of influence of natural and climatic conditions, social and economical activities on manufacturing and economical activity of social and economical system (territory, region, state). The informational system was worked out permitting to assess compensation of influence of negative natural and climatic factors optimal of social and economical activities with presented description of database of statistical information, algorithm of calculation, resulting screen forms.